'Trifecta' outcomes of robot‐assisted partial nephrectomy in solitary kidney: a Vattikuti Collective Quality Initiative (VCQI) database analysis. (16th August 2017) - Arora, Sohrab; Abaza, Ronney; Adshead, James M.; Ahlawat, Rajesh K.; Challacombe, Benjamin J.; Dasgupta, Prokar; Gandaglia, Giorgio; Moon, Daniel A.; Yuvaraja, Thyavihally B.; Capitanio, Umberto; Larcher, Alessandro; Porpiglia, Francesco; et al.
Abstract : Objectives: To analyse the outcomes of robot‐assisted partial nephrectomy (RAPN) in patients with a solitary kidney in a large multi‐institutional database. Patients and Methods: In all, 2755 patients in the Vattikuti Collective Quality Initiative database underwent RAPN by 22 surgeons at 14 centres in nine countries. Of these patients, 74 underwent RAPN with a solitary kidney between 2007 and 2016. We retrospectively analysed the functional and oncological outcomes of these 74 patients. A 'trifecta' of outcomes was assessed, with trifecta defined as a warm ischaemia time (WIT) of <20 min, negative surgical margins, and no complications intraoperatively or within 3 months of RAPN. Results: All 74 patients underwent RAPN successfully with one conversion to radical nephrectomy. The median (interquartile range [IQR]) operative time was 180 (142–230) min. Early unclamping was used in 11 (14.9%) patients and zero ischaemia was used in 12 (16.2%). Trifecta outcomes were achieved in 38 of 66 patients (57.6%). The median (IQR) WIT was 15.5 (8.75–20.0) min for the entire cohort. The overall complication rate was 24.1% and the rate of Clavien–Dindo grade ≤II complications was 16.3%. Positive surgical margins were present in four cases (5.4%). The median (IQR) follow‐up was 10.5 (2.12–24.0) months. The median drop in estimated glomerular filtration rate at 3 months was 7.0 mL/min/1.72 m 2 (11.01%). Conclusion: Our findings suggest that RAPN is a safe and effective treatment option for select renal tumours in solitary kidneys in terms of a trifecta of negative surgical margins, WIT of <20 min, and low operative and perioperative morbidity.